Empowering Border-Area Students Through Technology-Integrated Extensive Reading: A Community Service Initiative - Prancisca, Stella; Fergina, Ana; Ghazy, Ahmad; Ananda, Elsa; Aminah, Syarifah; Rizqi, Muhammad Ainur (Sekolah Tinggi Ekonomi dan Bisnis Syariah (STEBIS) Indo Global Mandiri, 2025)
This article presents a community service program conducted at SMAN 1 Sajingan Besar, a high school located near the Indonesia–Malaysia border. The program aimed to improve students’ interest and skills in reading English by introducing an easy and enjoyable reading approach. Over two days, students learned the difference between reading for understanding and reading for details, and were trained to use an online tool called MReader to track their reading progress. The program received enthusiastic responses, especially during quiz games and hands-on practice sessions. Students not only became more motivated to read but also learned how to use digital tools in their English learning. The activity helped create a fun and competitive learning environment and gave students practical experience in choosing and completing English books. The program showed that using technology in learning can increase student interest and reading habits. For lasting impact, regular training, better internet access, and more book options are recommended. This program has the potential to become a long-term solution to support literacy in remote border areas.